Television White Space Based Broadband Network ' s Coverage and CAPEX Performance for Rural Areas Connectivity in Tanzania - Ismail, Moses (Tanzania Journal of Engineering and Technology, 2023)
This study compared the CAPEX requirements for a television white space (TVWS) based broadband network and that of deploying the UMTS based mobile broadband networks to deliver broadband connectivity in areas with sparse population which characterize most of Tanzania rural. Like many developing countries, Tanzania has low Internet penetration, with penetration of just over 46% when multiple subscriptions are taken into account. The affected communities are mostly rural due to low population densities which make deployment of the mobile broadband to be much expensive in terms of costs. This limits the economic development potential in these areas given that the broadband connectivity and services is a key driver for the Fourth Industrial Revolution (4IR or Industry 4.0) and modern digital economy. Comparative between the coverage capability of the TVWS and UMTS family of standards by considering the number of base transceiver stations (BTS) is conducted to cover a specific geographic area for three different radio operating environments namely hilly, undulating and flat terrain landscapes. The broadband connectivity data rate is defined at the receiver rate of 2 Mbps or above, and used to determine the number of BTS required for the two technologies. Results show that introducing the TVWS as a middle mile solution, cuts the number of UMTS BTS required to serve the same population by 68%, 66.7%, and 75% for the three canonical environments respectively. Keywords: Broadband, connectivity, internet, TVWS